Genetic and Toxigenic Variability within Aspergillus flavus Population Isolated from Maize in Two Diverse Environments in Kenya - Okoth, Sheila; De Boevre, Marthe; Vidal, Arnau; Diana Di Mavungu, José; Landschoot, Sofie; Kyallo, Martina; Njuguna, Joyce; Harvey, Jagger; De Saeger, Sarah (Frontiers in Microbiology, 2018)
Aspergillus flavus is the main producer of carcinogenic aflatoxins in agricultural commodities such as maize. This fungus occurs naturally on crops, and produces aflatoxins when environmental conditions are favourable. The aim of this study is to analyse the genetic variability among 109 A. flavus isolates previously recovered from maize sampled from a known aflatoxin-hotspot (Eastern region, Kenya) and the major maize-growing area in the Rift Valley (Kenya), and to determine their toxigenic potential. DNA analyses of internal transcribed spacer (ITS) regions of ribosomal DNA, partial β-tubulin gene (benA) and calmodulin gene (CaM) sequences were used. The strains were further analysed for the presence of four aflatoxin-biosynthesis genes in relation to their capability to produce aflatoxins and other metabolites, targeting the regulatory gene aflR and the structural genes aflP, aflD, and aflQ. In addition, the metabolic profile of the fungal strains was unravelled using state-of-the-art LC-MS/MS instrumentation. The three gene-sequence data grouped the isolates into two major clades, A. minisclerotigenes and A. flavus. A. minisclerotigenes was most prevalent in Eastern Kenya, while A. flavus was common in both regions. A. parasiticus was represented by a single isolate collected from Rift Valley. Diversity existed within the A. flavus population, which formed several subclades. An inconsistency in identification of some isolates using the three markers was observed. The calmodulin gene sequences showed wider variation of polymorphisms. The aflatoxin production pattern was not consistent with the presence of aflatoxigenic genes, suggesting an inability of the primers to always detect the genes or presence of genetic mutations. Significant variation was observed in toxin profiles of the isolates. This is the first time that a profound metabolic profiling of A. flavus isolates was done in Kenya. Positive associations were evident for some metabolites, while for others no associations were found and for a few metabolite-pairs negative associations were seen. Additionally, the growth medium influenced the mycotoxin metabolite production. These results confirm the wide variation that exists among the group A. flavus and the need for more insight in clustering the group.